Spinal presentations in children with type 1 spinal muscular atrophy on nusinersen treatment across the SMA-REACH UK network: a retrospective national observational study - Francesco Muntoni; Giovanni Baranello; Pinki Munot; Mariacristina Scoto; Adnan Manzur; Marion Main; Evelin Milev; Lianne Abbott; Victoria Selby; Amy Wolfe; Annemarie Rohwer; Catherine Rye; et al. (BMJ Open)
Background Prior to the introduction of disease-modifying treatments (DMTs), children with type 1 spinal muscular atrophy (SMA) typically did not survive beyond the age of 2 years; management was mainly palliative. Novel therapies have made this a treatable condition, resulting in increased life expectancy and more time spent upright. Survival and improved function mean spinal asymmetry is a new complication with limited data on its prevalence and severity and no current guidelines on management and treatment. This study aimed to evaluate the spinal presentation and management of type 1 SMA children on nusinersen across the SMA-REACH UK network.Methods Spinal presentation and management of 80 children (age range 4 months–14 years, median 4 years 2 months) with type 1 SMA on nusinersen across the SMA-REACH UK network were reviewed through retrospective data analysis.Results There were 60 type 1 children who developed a spinal asymmetry, of which 40 had kyphosis and 50 used a supportive thoraco-lumbar-sacral orthosis (TLSO). TLSOs were predominantly a one-piece jacket with abdominal hole, advised to be worn when upright during the day. Reduced neck range of movement was found in 33, 1 of these had plagiocephaly and 5 had torticollis. Of those with reduced neck range of movement, 26 (79%) had spinal asymmetry. Spinal surgery was performed in 7.Conclusions Our study confirms high prevalence of spinal asymmetry in this cohort, requiring long-term management planning. It provides information on presentation and treatment options, facilitating development of guidelines for these new complications observed in children surviving longer with DMTs.